New Zealand’s freshwater disaster - Joy, Mike (New Zealand Science Review, 2014)
Freshwater ecosystems in New Zealand have been under considerable and increasing stress since European colonisation. The draining of ninety per cent of wetlands and the removal of a similar amount of indigenous vegetation cover has placed much strain on the health of freshwater bodies. These changes wrought massive impacts through the loss of the crucial hydrologic and biological functions performed by intact wetland and forest ecosystems. These impacts have been exacerbated by the more recent intensification of farming, with the concomitant addition of excess nutrients and sediment to water as well as the effects of urbanisation and introductions of exotic fish species. The cumulative impacts of all these changes can be seen with declining water physicochemical measures and the biological status of freshwater ecosystems. The most obvious impacts are revealed by biological indicators, with seventy-four per cent of the native freshwater fish species listed as threatened, and ninety per cent of lowland waterways and sixty-two per cent of all waterways failing bathing standards. Lowland lakes are under immense pressure; forty-four per cent of monitored lakes are eutrophic or worse and they are mostly the lowland lakes. The legislative response from central and local government to the obvious declines has failed to halt or even slow the deterioration. In contrast, government initiatives to increase farming intensification mean there is no chance of improvement, and further declines will be the future for New Zealand freshwaters.